Assessing geographical differences in illicit drug consumption—A comparison of results from epidemiological and wastewater data in Germany and Switzerland. (1st April 2016) - Been, Frederic; Bijlsma, Lubertus; Benaglia, Lisa; Berset, Jean-Daniel; Botero-Coy, Ana M.; Castiglioni, Sara; Kraus, Ludwig; Zobel, Frank; Schaub, Michael P.; Bücheli, Alexander; Hernández, Félix; Delémont, Olivier; et al.
Highlights: Comparison of epidemiological, crime and wastewater data about illicit drug use. Improve understanding of wastewater results from an epidemiological point of view. Complementary results were obtained for less stigmatised drugs (e.g. cannabis). Wastewater analysis highly relevant for more stigmatised drugs (e.g. cocaine). Useful to detect and understand geographical features in drug use. Abstract: Background: Wastewater analysis is an innovative approach that allows monitoring illicit drug use at the community level. This study focused on investigating geographical differences in drug consumption by comparing epidemiological, crime and wastewater data. Methods: Wastewater samples were collected in 19 cities across Germany and Switzerland during one week, covering a population of approximately 8.1 million people. Self-report data and consumption offences for the investigated areas were used for comparison and to investigate differences between the indicators. Results: Good agreement between data sources was observed for cannabis and amphetamine-type stimulants, whereas substantial discrepancies were observed for cocaine. In Germany, an important distinction could be made between Berlin, Dortmund and Munich, where cocaine and particularly amphetamine were more prevalent, and Dresden, where methamphetamine consumption was clearly predominant. Cocaine consumption was relatively homogenous in the larger urban areas of Switzerland, although prevalence and offences data suggested a more heterogeneous picture. Conversely, marked regional differences in amphetamine and methamphetamine consumption could be highlighted. Conclusions: Combining the available data allowed for a better understanding of the geographical differences regarding prevalence, typology and amounts of substances consumed. For cannabis and amphetamine-type stimulants, the complementarity of survey, police and wastewater data could be highlighted, although notable differences could be identified when considering more stigmatised drugs (i.e. cocaine and heroin). Understanding illicit drug consumption at the national scale remains a difficult task, yet this research illustrates the added value of combining complementary data sources to obtain a more comprehensive and accurate picture of the situation.